Diagnostic potential of urinary CX3CL1 for amnestic mild cognitive impairment and Alzheimer’s disease - Xu, Yali; Zhang, Jie; Shen, Ying-Ying; Li, Wei-Wei; Li, Bin; Cheng, Hai-Ping; Zeng, Gui-Hua (Frontiers in Aging Neuroscience, 2025)
IntroductionThe role of the chemokine CX3CL1 in the processes of aging and Alzheimer’s disease (AD) pathogenesis is well-established. This study aims to evaluate the diagnostic potential of urinary CX3CL1 levels in distinguishing between AD patients, those experiencing amnestic mild cognitive impairment (aMCI), and cognitively normal (CN) individuals.MethodsA cohort comprising 516 CN individuals across various age groups, 102 AD patients, and 65 subjects with aMCI was assembled, alongside 93 age- and sex-matched CN controls. Enzyme-linked immunosorbent assay (ELISA) was utilized to quantify urinary CX3CL1 levels.ResultsUrinary CX3CL1 concentrations exhibited an age-dependent increase and demonstrated a positive correlation with age. Comparatively, AD patients exhibited significantly elevated urinary CX3CL1 levels when contrasted with both the CN controls and the aMCI cohort. Conversely, aMCI patients displayed urinary CX3CL1 levels that were notably reduced in comparison to both the AD and CN groups.ConclusionUrinary CX3CL1 levels correlate with the aging process and may serve as a potential diagnostic biomarker for both amnestic mild cognitive impairment (aMCI) and Alzheimer’s disease (AD).